ASSOCIATION OF rs4537545 (C>T) ALLELE POLYMORPHISM IN THE IL6R GENE WITH THE DEVELOPMENT OF RHEUMATOID ARTHRITIS - L. Topchieva V.; I. Malysheva E.; O. Balan V.; I. Marusenko M.; O. Barysheva Yu.; Л. Топчиева В.; И. Малышева Е.; О. Балан В.; И. Марусенко М.; О. Барышева Ю. (Rheumatology Science and Practice, 2020)
Objective: to analyze the association of the polymorphic marker rs4537545 (C>T) in the IL6R gene with the development of rheumatoid arthritis (RA) in the population of the Republic of Karelia. Subjects and methods. The investigation included 190 samples of DNA extracted from the whole blood of healthy individuals and 158 samples from patients with RA. Genotyping was performed using a polymerase chain reaction (PCR)-restriction fragment length polymorphism analysis. The expression level of IL6 and IL6R genes in peripheral blood leukocytes (PBLs) from healthy individuals was assessed by real-time PCR. The plasma content of interleukin-6 (IL-6) in healthy donors was measured by enzyme-linked immunosorbent assay (ELISA). Results and discussion. An association of the polymorphic marker rs4537545 (C>T) in the IL6R gene with the development of rheumatoid arthritis was found in the population of the Republic of Karelia. The risk of RA in the persons carrying the T-allele of rs4537545 in the genotypes was 2.1 times higher than that in the C-allele carriers (odds ratio (OR), 2.103; 95% confidence interval, 1.032-4.287). The genotypes were ascertained to have an effect on the level of IL6R gene in PBL and on the plasma content of IL-6 in the healthy donors. Conclusion. The polymorphic marker rs4537545 (C>T) in the IL6R gene is involved in the genetic predisposition of humans to RA development through modulation of the level of transcriptional activity of the IL6R gene and the content of IL-6. Цель исследования – анализ ассоциации полиморфного маркера rs4537545 (C>T) гена IL6R с развитием ревматоидного артрита (РА) у населения Республики Карелия. Материал и методы. В исследование включено 190 образцов ДНК, выделенной из цельной крови здоровых людей, и 158 образцов от пациентов с РА. Генотипирование проводили с помощью анализа полиморфизма длин рестрикционных фрагментов на основе полимеразной цепной реакции (ПЦР). Уровень экспрессии генов IL6 и IL6R в лейкоцитах периферической крови (ЛПК) здоровых людей оценивали с помощью ПЦР в режиме реального времени. Содержание интерлейкина 6 (ИЛ6) в плазме крови здоровых доноров измеряли с помощью иммуноферментного анализа (ИФА). Результаты и обсуждение. Обнаружена ассоциация полиморфного маркера rs4537545 (C>T) гена IL6R с развитием РА у населения Республики Карелия. У лиц, имеющих в генотипе аллель Т по rs4537545, риск развития РА в 2,1 раза выше, чем у носителей алелля С (отношение шансов 2,103; 95% доверительный интервал 1,032–4,287). Обнаружено влияние генотипов по указанному маркеру на уровень экспрессии гена IL6R в ЛПК и содержание ИЛ6 в плазме крови здоровых доноров. Заключение. Полиморфный маркер rs4537545 (C>T) гена IL6R вовлечен в генетическую предрасположенность людей к развитию РА через модулирование уровня транскрипционной активности гена IL6R и содержания ИЛ6.